Status of Internet use for Higher Education and Research in Agricultural Sciences (The Agriculturists, 2012)
A study was conducted to explore the role of internet on higher education and research at two selected public universities in Bangladesh, which offer courses on Agricultural Sciences. One hundred and fifty eight teachers and 79 post-graduate students were interviewed based on questionnaires. It was found that 90.8% teachers had internet connectivity and they used internet on regular basis to search relevant websites and download the selected course contents. All the teachers agreed that adequate and reliable information on different topics of Agricultural Sciences can be obtained through internet, which can be used for academic and research purposes. Use of internet by the students is being gradually increased in public universities. The universities are expanding the internet facilities to increase services to the teaching and learning communities. Digitization of libraries and internet links between the public universities libraries are in progress.  It is expected that the use of internet would bring significant changes in higher education and research systems of developing nations and the institutions of higher education would attain a global standard. Development of education in these countries are badly influenced by limited resource and poor finance.DOI: http://dx.doi.org/10.3329/agric.v10i1.11063The Agriculturists 2012; 10(1): 38-45